2016
DOI: 10.1183/13993003.01201-2015
|View full text |Cite
|
Sign up to set email alerts
|

“Scar-cinoma”: viewing the fibrotic lung mesenchymal cell in the context of cancer biology

Abstract: Lung cancer and pulmonary fibrosis are common, yet distinct, pathological processes that represent urgent unmet medical needs. Striking clinical and mechanistic parallels exist between these distinct disease entities. The goal of this article is to examine lung fibrosis from the perspective of cancer-associated phenotypic hallmarks, to discuss areas of mechanistic overlap and distinction, and to highlight profibrotic mechanisms that contribute to carcinogenesis. Ultimately, we speculate that such comparisons m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 168 publications
(226 reference statements)
1
31
0
Order By: Relevance
“…[11] Studies evaluating fibrotic biopsies from patients with idiopathic pulmonary fibrosis (IPF) have shown a paucity of apoptosis, similar to that of malignancies, which may indicate a synonymous ability of both fibrotic and malignant tissue to evade cell death. [2,10] A possible explanation for this lack of apoptosis could be explained by overexpression of anti-apoptotic protein kinases, such as survivin. [12] Furthermore, the process of autophagy, by which cell death occurs via the lysosomal pathway, has been shown to be impaired in IPF as well as fibroblast models.…”
Section: Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…[11] Studies evaluating fibrotic biopsies from patients with idiopathic pulmonary fibrosis (IPF) have shown a paucity of apoptosis, similar to that of malignancies, which may indicate a synonymous ability of both fibrotic and malignant tissue to evade cell death. [2,10] A possible explanation for this lack of apoptosis could be explained by overexpression of anti-apoptotic protein kinases, such as survivin. [12] Furthermore, the process of autophagy, by which cell death occurs via the lysosomal pathway, has been shown to be impaired in IPF as well as fibroblast models.…”
Section: Researchmentioning
confidence: 99%
“…[1] The presence of dense hyaline scarring in the centre of many primary peripheral lung carcinomas led to recognition of the phenomenon of a lung scar carcinoma, although it was not clear whether the relevant area of scarring preceded the carcinoma or was caused by the carcinoma. [1,2] In recent years there has been renewed interest in scar carcinomas, also referred to as 'scar-cinomas' . [2] It has been reported that the presence of large numbers of fibroblasts and myofibroblasts is a hallmark of carcinomas.…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations